Endobronchial ultrasound-guided cryobiopsy of a rare epicardial tumour - Toshiyuki Nakai; Atsushi Miyamoto; Mana Ogawa; Akimasa Morisaki; Nobuhiro Izumi; Sayaka Tanaka (Pulmonology)
Background Cardiac tumors are rare, and a nonsurgical diagnosis is preferred for determining appropriate treatment strategies.Research Question Can Endobronchial ultrasound-guided cryobiopsy (EBUS-cryo) be useful for diagnosing cardiac tumors?Study Design and Methods This paper presents a case report on the successful diagnosis of a rare cardiac tumor using EBUS-cryo. A 60-year-old woman was referred to our hospital after echocardiography revealed an epicardial tumor compressing the bilateral atria. Computed tomography revealed a 90-mm cardiac tumor adjacent to the tracheal bifurcation compressing the surrounding large vessels. Endobronchial ultrasound-guided cryobiopsy (EBUS-cryo) was performed, and a histological diagnosis of schwannoma, a type of peripheral nerve sheath tumor (PNST), was made without severe complications. Surgical resection was performed, and the tumor was found to originate from the pericardium on the left atrial wall.Results The surgical specimens contained small areas of perineurioma in addition to schwannoma, leading to the final diagnosis of extremely rare hybrid PNST.Conclusion EBUS-cryo can be one of useful biopsy techniques for diagnosing cardiac tumors.